Size distributions of fine silicate and other particles in Masaya's volcanic plume - Martin, R. S.; Mather, T. A.; Pyle, D. M.; Power, M.; Tsanev, V. I.; Oppenheimer, C.; Allen, A. G. [UNESP]; Horwell, C. J.; Ward, E. P. W. (Amer Geophysical Union, 2009)
Direct-sampling and remote-sensing measurements were made at the crater rim of Masaya volcano (Nicaragua) to sample the aerosol plume emanating from the active vent. We report the first measurements of the size distribution of fine silicate particles (d <10 mu m) in Masaya's plume, by automated scanning electron microscopy (QEMSCAN) analysis of a particle filter. The particle size distribution was approximately lognormal with modal d similar to 1.15 mu m. The majority of these particles were found to be spherical. These particles are interpreted to be droplets of quenched magma produced by a spattering process. Compositional analyses confirm earlier reports that the fine silicate particles show a range of compositions between that of the degassing magma and nearly pure silica and that the extent of compositional variability decreases with increasing particle size. These results indicate that fine silicate particles are altered owing to reactions with acidic droplets in the plume. The emission flux of fine silicate particles was estimated as similar to 10(11) s(-1), equivalent to similar to 55 kg d(-1). Sun photometry, aerosol spectrometry, and thermal precipitation were used to determine the overall particle size distribution of the plume (0.01 < d(mu m) < 10). Sun photometry and aerosol spectrometry measurements indicate the presence of a large number of particles (assumed to be aqueous) with d similar to 1 mu m. Aerosol spectrometry measurements further show an increase in particle size as the nighttime approached. The emission flux of particles from Masaya was estimated as similar to 10(17) s(-1), equivalent to similar to 5.5 Mg d(-1) where d < 4 mu m.